The Libyans and the Peoples of the Sea (1224-1190 BC) (Journal of Human Sciences, 2023)
The Libyan-European relations are very old. As a result of the proximity of the Libyan shores in Cyrenaica to the islands of the Mediterranean Sea, trade relations arose between the Libyan tribes in Cyrenaica and Crete. The Al-Mushush tribe was in contact with the Sherdon in Crete for seventy years before their alliance with the Libyans during the reign of Pharaoh Merneptah.  . The Sea Peoples (Achaeans, Aeolians, Ionians and Dorians) are Indo-European peoples and tribes that migrated from eastern northern Europe, eastern Caspian Sea, and central Asia in successive batches to the Balkan Peninsula (Greece), and to the coasts and islands of the Aegean Sea, as a result of population pressure, drought, attraction and wars.  Competition and conflict over the Mediterranean trade. The sea peoples headed from the island of Crete to Cyprus and from there headed to the Libyan coast in a mass migration of men, women and children. The sea peoples landed on the Libyan coast at the end of the thirteenth century and the beginning of the twelfth century BC and mixed with the Libyans. They then were subject to their leadership, customs and systems. The Libyan tribes constituted a source of threat to the pharaohs’ kings since the dawn of pharaonic history. The pharaonic inscriptions recorded news of attacks and wars between the Libyan tribes and the pharaohs. The Libyans and the Sea Peoples allied themselves and attacked Egypt during the reign of Pharaoh Merneptah in 1219 BC, as well as the alliance of the Libyans and the Sea Peoples during the reign of Pharaoh Ramses III in 1193 BC. and attacked Egypt, and the leadership in the two attacks was in the hands of Libya.